PENDAPATAN NASIONAL DALAM PERSPEKTIF EKONOMI ISLAM: KAJIAN DAN TEORITIS - Serliyana Serliyana; Syahriyah Semaun (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2026)
This study examines the concept of national income comprehensively in both conventional and Islamic economics. The main objective of this research is to gain a more complete understanding of the definition of national income as well as the Islamic economic perspective on this concept. This study uses a literature review method by analyzing various sources related to national income in both conventional and Islamic economics. The findings show that Islamic economics places justice, equitable distribution, and compliance with Sharia principles as the main foundations in managing national income. Instruments such as zakat, infaq, sadaqah, waqf, jizyah, kharaj, and ushr function as redistribution mechanisms to reduce social inequality. Therefore, national income in Islamic economics is not only oriented toward growth, but also toward achieving comprehensive and equitable societal welfare.